Functional analysis of novel DEAF1 variants identified through clinical exome sequencing expands DEAF1‐associated neurodevelopmental disorder (DAND) phenotype. Issue 12 (23rd September 2017) - Chen, Li; Jensik, Philip J.; Alaimo, Joseph T.; Walkiewicz, Magdalena; Berger, Seth; Roeder, Elizabeth; Faqeih, Eissa A.; Bernstein, Jonathan A.; Smith, Ann C. M.; Mullegama, Sureni V.; Saffen, David W.; Elsea, Sarah H.
Abstract: Deformed epidermal autoregulatory factor‐1 (DEAF1), a transcription factor essential for central nervous system and early embryonic development, has recently been implicated in a series of intellectual disability‐related neurodevelopmental anomalies termed, in this study, as DEAF1 ‐associated neurodevelopmental disorder (DAND). We identified six potentially deleterious DEAF1 variants in a cohort of individuals with DAND via clinical exome sequencing (CES) and in silico analysis, including two novel de novo variants: missense variant c.634G > A p.Gly212Ser in the SAND domain and deletion variant c.913_915del p.Lys305del in the NLS domain, as well as c.676C > T p.Arg226Trp, c.700T > A p.Trp234Arg, c.737G > C p.Arg246Thr, and c.791A > C p.Gln264Pro. Luciferase reporter, immunofluorescence staining, and electrophoretic mobility shift assays revealed that these variants had decreased transcriptional repression activity at the DEAF1 promoter and reduced affinity to consensus DEAF1 DNA binding sequences. In addition, c.913_915del p.K305del localized primarily to the cytoplasm and interacted with wild‐type DEAF1. Our results demonstrate that variants located within the SAND or NLS domains significantly reduce DEAF1 transcriptional regulatory activities and are thus, likely to contribute to the underlying clinical concerns in DAND patients. These findings illustrate the importance of experimental characterization of variants with uncertain significance identified by CES to assess their potential clinical significance and possible use in diagnosis. Abstract : We identified six potentially deleterious DEAF1 variants in individuals with DEAF1‐associated‐neurodevelopmental‐disorder (DAND) via clinical‐exome‐sequencing (CES) and in silico analysis, including two novel de novo variants c.634G > A p.Gly212Ser and c.913_915del p.Lys305del. Functional assays revealed that these variants had decreased transcriptional repression activity and reduced DNA binding. In addition, c.913_915del p.K305del localized primarily to the cytoplasm and interacted with wild‐type DEAF1. Our results illustrate the importance of experimental characterization of variants identified by CES to assess their contribution to DAND.